Malignant Melanoma of the External Auditory Canal on 68Ga-FAPI PET/CT. (24th June 2023) - Liu, Ya; Ding, Haoyuan; Wan, Zibei; Fan, Dongmei; Huang, Zhanwen
Abstract: External ear melanomas are relatively rare and usually occur in the regions of helix and ear lobes. Rarer still are primary melanomas of the external auditory canal. We report findings of melanoma of the external auditory canal on 68 Ga-FAPI PET/CT in a 56-year-old man who presented with sharp pain in the external auditory canal for 7 months.